A new species of Setosabatieria Platt, 1985(Nematoda: Comesomatidae) from Chek Jawa,Singapore, with a key to valid species of the genus - Cheng, Ann Chen; Shabdin, Mohd Long (Taylor & Francis Ltd., 2014)
A new species of Comesomatidae Filipjev, 1918 is described from an intertidal sandy–muddy beach at Chek Jawa, Singapore. Setosabatieria singaporensis sp. nov. is characterized by having an amphideal fovea with 2.75–3.0 turns, 14–17 cervical setae per row, 17–20 small precloacal supplements, arcuate spicules with a central cuticularized strip, a leaf-like cuticle extension and gubernacular apophyses bent ventrally in the distal portion. A key to all valid species of Setosabatieria is provided